Implementasi Peraturan Bupati Kab. Bandung No. 78 Tahun 2021 Tentang Pembelajaran Pendidikan Keagamaan di Sekolah Dasar Desa Gunungleutik - Baehaqi, Riyandi; Rahminawati, Nan; Rachmah, Huriah (Bandung Conference Series: Islamic Education, 2024)
Abstract. This research is entitled Implementation of District Regent Regulations. Bandung No. 78 of 2021 concerning Religious Education Learning at Gunungleutik Village Elementary Schools, this program was created to overcome Al-Qur'an illiteracy in Bandung Regency through the Koran School program. This research aims to identify the learning and benefits of Koran reading teachers at the Gunungleutik village elementary school in the Bandung Regency Koran School program. The method used is a qualitative method with a phenomenological approach and the research instruments used are interviews, observation and documentation, data analysis techniques using data reduction, data display, and drawing conclusions and verification. This Quran Reciting School Program has a positive impact on the school, especially PAI teachers, helping to facilitate learning that is not affordable in Islamic Religious Education learning, so Koran Koran teachers provide facilities to provide additional material related to Reading and Writing Memorizing the Al-Qur'an. The shortcomings of this program are clashes in teaching and learning hours, some of which are used by Koran teachers, and the lack of competence of Koran teachers in preparing and developing material. The purpose of the District Regent's Regulations. Bandung No. 78 of 2021 concerning Religious Education Learning in the form of the Koran School program targeting elementary school level students in reducing Al-Qur'an illiteracy, the school is grateful to get the benefits of its students experiencing positive development in reading, writing, and memorizing the Al-Qur'an. and to students. Abstrak. Penelitian ini dengan judul Implementasi Peraturan Bupati Kab. Bandung No. 78 Tahun 2021 Tentang Pembelajaran Pendidikan Keagamaan di Sekolah Dasar Desa Gunungleutik, program ini dibuat untuk mengatasi buta huruf Al-Qur’an di Kabupaten Bandung melalui program Sekolah Mengaji . Tujuan penelitian ini untuk mengidentifikasi pembelajaran dan manfaat guru ngaji di sekolah dasar desa Gunungleutik dalam program Sekolah Mengaji Kabupaten Bandung. Metode yang digunakan yaitu metode kualitatif dengan pendekatan fenomenologi dan instrumen penelitian yang digunakan adalah wawancara, observasi dan dokumentasi, teknik analisis data menggunakan reduksi data, data display dan penarikan kesimpulan dan verifikasi. Program Sekolah Mengaji ini berdampak positif terhadap pihak sekolah khususnya guru PAI membantu memfasilitasi pembelajaran yang tidak terjangkau dalam pembelajaran PAI, jadi guru ngaji memberikan fasilitas untuk memberikan tambahan materi terkait Baca Tulis Hafal Al-Qur'an. kekurangan pada program ini bentroknya jam KBM yang sebagian di pakai oleh guru ngaji dan kurangnya kompetensi guru ngaji dalam persiapan dan pengembangan materi. Tujuan dari Peraturan Bupati Kab. Bandung No. 78 Tahun 2021 Tentang Pembelajaran Pendidikan Keagamaan dalam bentuk program Sekolah Mengaji dengan sasaran peserta didik jenjang sekolah dasar dalam mengurangi buta huruf Al-Qur’an, pihak sekolah bersyukur mendapatkan manfaat para peserta didiknya mengalami perkembangan positif dalam membaca, menulis dan menghafal Al-Qur'an pada siswa.